Peningkatan Keterampilan Mengajar Guru IPA Menggunakan Google Sites - Khusaini, Khusaini; Kusairi, Sentot; Kurniawan, Bakhrul Rizky (LPkM Universitas Bakrie, 2025)
Natural Science Subject Teachers' Conference (MGMP IPA) in Malang City is a community of science teachers who actively discuss and collaborate to enhance their professionalism. However, science teachers still face major challenges when implementing the independent curriculum; one of them is using ICT-based science learning media. This problem shows the need for training to carry out empowerment activities for science teachers in the MGMP Malang to develop Google Sites as ICT-based learning media. This community service applied the five-stage method: socialization, training, application of technology, mentoring and evaluation, and program sustainability. Teachers can upload the results of several works that have been compiled on Google Sites, consisting of learning objectives, materials, photos of activities, assessments, and other learning resources that are connected to Google Apps, so that teachers can access them at any time. Teachers use online media such as Quizizz, Kahoot, and Spinner for the assessment component. Overall, based on the results of the teachers’ questionnaire and the products made, it is indicated that this community service has succeeded in providing direct experience, which triggered teachers’ enthusiasm to use Google Sites as an interesting and meaningful learning medium in the class. These findings showed the program helped the teachers to enhance their professionalism.